The relationship of alpha-synuclein to mitochondrial dynamics and quality control - Thorne, Naomi J.; Tumbarello, David A. (Frontiers in Molecular Neuroscience, 2022)
Maintenance of mitochondrial health is essential for neuronal survival and relies upon dynamic changes in the mitochondrial network and effective mitochondrial quality control mechanisms including the mitochondrial-derived vesicle pathway and mitophagy. Mitochondrial dysfunction has been implicated in driving the pathology of several neurodegenerative diseases, including Parkinson’s disease (PD) where dopaminergic neurons in the substantia nigra are selectively degenerated. In addition, many genes with PD-associated mutations have defined functions in organelle quality control, indicating that dysregulation in mitochondrial quality control may represent a key element of pathology. The most well-characterised aspect of PD pathology relates to alpha-synuclein; an aggregation-prone protein that forms intracellular Lewy-body inclusions. Details of how alpha-synuclein exerts its toxicity in PD is not completely known, however dysfunctional mitochondria have been observed in both PD patients and models of alpha-synuclein pathology. Accordingly, an association between alpha-synuclein and mitochondrial function has been established. This relates to alpha-synuclein’s role in mitochondrial transport, dynamics, and quality control. Despite these relationships, there is limited research defining the direct mechanisms linking alpha-synuclein to mitochondrial dynamics and quality control. In this review, we will discuss the current literature addressing this association and provide insight into the proposed mechanisms promoting these functional relationships. We will also consider some of the alternative mechanisms linking alpha-synuclein with mitochondrial dynamics and speculate what the relationship between alpha-synuclein and mitochondria might mean both physiologically and in relation to PD.